2020
DOI: 10.1080/20002297.2020.1857998
|View full text |Cite
|
Sign up to set email alerts
|

Salivary bacterial shifts in oral leukoplakia resemble the dysbiotic oral cancer bacteriome

Abstract: Objective : While some oral carcinomas appear to arise de novo , others develop within long-standing conditions of the oral cavity that have malignant potential, now known as oral potentially malignant disorders (OPMDs). The oral bacteriome associated with OPMD has been studied to a lesser extent than that associated with oral cancer. To characterize the association in detail we compared the bacteriome in whole mouth fluid (WMF) in patients with oral leukoplakia, oral cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 45 publications
2
36
1
Order By: Relevance
“…The surface samples may depict colonizing microbiome, whereas deeper tissue samples might reflect more significant microbiota that may play a potential role. Salivary samples may be reflective of the total oral environment, whereas direct sampling from tissue samples may be more representative of an endogenous microbiome co-evolving with the host [ 42 ]. The microbial communities collected from the mucosal surface by an oral swab may not reflect the tumor-associated microbiome [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surface samples may depict colonizing microbiome, whereas deeper tissue samples might reflect more significant microbiota that may play a potential role. Salivary samples may be reflective of the total oral environment, whereas direct sampling from tissue samples may be more representative of an endogenous microbiome co-evolving with the host [ 42 ]. The microbial communities collected from the mucosal surface by an oral swab may not reflect the tumor-associated microbiome [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Decsi et al found 43 different species in OPMD compared to 18 species in the healthy mucosa, with only 8 shared by both tissues [11]. These results question the validity of whole-mouth sampling in oral leukoplakia since it may be altered by periodontal disease or dental caries [12].…”
Section: The First Dilemma: What To Samplementioning
confidence: 99%
“…Nonetheless, other saliva-based studies were able to identify significant differences in the microbiome composition between OLK and healthy controls [12,[15][16][17][18]. Moreover, although through a highly biased study (i.e., time lag between OLK and sampling; lack of histologic assessment of OLK), Shridhar et al showed a better proportion of quantifiable pathogens from salivary rinse rather than gingival swabs for three selected species [18].…”
Section: The First Dilemma: What To Samplementioning
confidence: 99%
See 2 more Smart Citations